(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the structure of a dictionary entry in a glossary based on the experience of scientific works. Detailed information is provided on the fact that a term consists of many components and, as a result, the inconveniences in its use, in which a term serving to express one concept consists of two, three or more components.